Comparison of general practitioner consultations among Chinese patients with different reasons for visits: a multimethod investigation. (November 2020) - Zhong, Chenwen; Luo, Zhuojun; Liang, Cuiying; Zhou, Mengping; Kuang, Li
Abstract: Background: The reasons for visits (RFVs) of patients reflect their needs and health problems when they enter the health system. It is important for general practitioners to identify and target appropriate health care for patients with different RFVs. How general practitioners interact with different patients during consultations remained unknown in China. Our study aimed to compare the content of general practitioner consultations among Chinese patients with different RFVs. Methods: We did a multimethod investigation of general practitioner consultations in eight community health centres in Guangdong, China. We collected data on visits to general practitioners by direct observation and audiotape, and coded the data with a modified Davis Observation Code. We adopted a nested sampling method and recruited a total of 17 eligible general practitioners and 445 patients. Inclusion criteria for general practitioners were rich clinical experience, large volume of outpatient visits per day, and signed informed consent to participate in the study. Eligible patients had to be older than 18 years and verbally agree to participate in this study. We collected general practitioner and patient characteristics including RFV with a post-visit survey. We compared general practitioner consultation using a general linear model adjusted for patient characteristics and health-care use factors. We obtained written informed consent from all general practitioners and informed verbal consent from all patients. Ethical approval was obtained from the Institutional Review Board of the School of Public Health, Sun Yat-Sen University, China. The protocol for this study conforms to the guidelines of the 1975 Declaration of Helsinki. Findings: Between Jul 2, 2018 and Jan 16, 2019, we collected data on 445 visits to general practitioners. Chronic illness (212 [48%]), acute illness (188 [42%]), and health counselling (30 [7%]) were the three major reasons for visits, while the remaining reasons included health examination and rehabilitation (15 [3%]). The mean duration of visits were 5·6 min (SD 3·8) for chronic illness visits, 4·8 min (SD 2·7) for acute illness visits, and 6·5 min (SD 4·1) for health counselling visits. Treatment planning was the leading content of general practitioner consultation among all three groups. However, for the chronic illness group, general practitioners spent more time in negotiation for drug costs (29·2%, SD 25·8 for chronic illness vs 15·8%, SD 15·1 for acute illness vs 11·1%, SD 14·7 for health counselling; p<0·0001), but less time on taking patient history (28·1%, SD 27·6 for chronic illness vs 40·7%, SD 19·6 for acute illness vs 37·9%, SD 18·1 for health counselling; p=0·028) and physical examination (12·4%, SD 13·4 for chronic illness vs 21·1%, SD 15·5 for acute illness vs 18·3%, SD 14·6 for health counselling; p<0·0001). Interpretation: The mean duration of general practitioner consultations in China was shorter than that shown by studies in other countries. Treatment planning remained the most important content of general practitioner consultation regardless of patient RFV, although drug prescription was more of a concern among patient visits for chronic illness. This finding might provide evidence for health service planning and general practitioner training. Funding: The National Natural Science Foundation of China (grant 71673311).